About solving the Korteweg–de Vries equation with step-like initial data - Gladka, Z.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The solvability of a Cauchy problem for the Korteweg–de Vries equation is established, and the rate of decrease of solutions as a function of the smoothness of the potential is found.